The End of Victory : Prevailing in the Thermonuclear Age - Kaplan, Edward A. (Book collections on Project MUSE., 2022)
"The End of Victory tells the history of the enigmatic Net Evaluation Subcommittee of the National Security Council. The NESC studied the gravest potential failure of American strategy in the 1950s and '60s: a surprise Soviet nuclear attack. Its annual reports and specialized studies quantified the risks that Presidents Eisenhower and Kennedy faced in a decade rife with crises, from Berlin to Cuba. The detailed work of the NESC, whose very existence was secret until the mid-1980s, has only been available to researchers in any detail since 2014. Kaplan's is the first study of the NESC as a body, documenting its value to Cold War history and strategy"--